Dynamics of natural tree regeneration after strip-mining in the Amazon - Salomão, Rafael Paiva; Rosa, Nélson Araújo; Morais, Kácio Andrey Câmara (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
Forest restoration on strip mines is done with many native species in an effort to enrich floral composition and accelerate soil protection, along with the replacement of top soil and its contained seed bank. The aims of this study are to analyze the dynamics and structure of natural tree regeneration, identify the trees’ seeds and their dispersers, elaborate a set of indicators for the dynamics of tree regeneration, and to rank reforested areas on a year by year basis at the Mineração Rio do Norte bauxite strip mine in the Saracá-Taquera National Forest in Porto Trombetas, Pará state, northern Brazil. The study is based on the results of monitoring 26 permanent forest plots over four years (2001-2005) in areas reforested by the mining company between 1981-1987 and 1992-1996. All trees over 1,5 m in height were sampled. Of the observed tree regeneration, it is possible to conclude the followuing: (i) more tree species are found in younger areas (9-13 years of reforesting) than in older ones (18-24 years); (ii) the oldest areas show the largest annual increase in number of tree species; (iii) tree abundance (individuals per ha) tend to be greater in younger areas; (iv) the annual recruitment rate tends to be higher in older areas than in younger ones; (vi) annual mortality rates are greater in younger areas than in older ones; (vii) the annual turnover rate is much greater in older areas; (viii) turnover time is greater in younger areas; (ix) medium tree diameter was practically constant during the monitoring period; (x) the annual increase in basal area is greater in older areas than in young ones; (xi) the median total height is greater in younger areas than in older ones; (xii) many tree species are dispersed by more than one agent and more than 80% of the monitored tree species are dispersed by animals whose role in ecological succession is fundamental; (xiii) the plots reseeded in 1992 are ranked as having the best forest regeneration, whereas those from 1987, on the other extreme, exhibit the most problems; (xiv) research on top soil management is needed in areas strongly impacted by human activities that are to be reforested; (xv) forestry practices and soil preparation should also be refined in order to accomplish efficient forest restoration where the objective is to maximize tree diversity and biomass, especially of well-adapted, fast-growing native species.